Relação entre a qualidade tradicional e a mudança de cultura organizacional utilizando como metodologia o Círculo de Controle de Qualidade (CCQ) - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Aggregate value is to give a quality leap in one or more characteristics to a product, and make a difference of point of view to the customer. This article expresses a proposal for the implementation of the Quality Control Circle (QCC) as a strategic tool to improve the production process through the addition of value and eliminating waste, using together the traditional quality model, to obtain a culture change, where any collaborator becomes a final customer representative, eliminating waste through QCC projects.
Keywords: Círculo de Controle da Qualidade; Eliminação de desperdício; Adição de Valor; Mudança de cultura; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO